Advanced Functional Materials - Woo, Hee-Gweon.; Li, Hong.; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
With recent developments in the polymer, ceramic, sensor, and fuel cell technology, a range of novel materials have been manufactured for advanced, compact, and electronic industry. Polymers, silicon, energy materials have received much attention in recent years. "Advanced Functional Materials" gives the most recent research results on polymer, fine ceramics, sensor, and green fuel cells. The content of this book, mainly based on the authors' recent research results, covers a broad spectrum including: the advanced inorganic-organic-hybrid polymeric materials, high functional sensor, and microbial fuel cells. The book is suitable for the researchers working in the areas of polymer, nanotechnology, ceramic engineering, engineering thermoplastic, energy and power engineering, chemical engineering and materials, etc. Hee-Gweon Woo is a professor at the Department of Chemistry, Chonnam National University, the Republic of Korea. Hong Li is a professor at the Institute of Polymer Chemistry, Nankai University, China.
High Performance Organic Polymers -- Advanced Biodegradable Organic Polymers -- High Functional Inorganic Polymers -- Ceramic Composites from Inorganic Preceramic Polymers -- Chemical and Biological Sensors Based on Porous Silicon Nanomaterials -- Microbial Fuel Cells as the Real Source of Sustainable Energy.
Electronic reproduction.
Keywords: Molecular electronics -- Materials; Electrooptics -- Materials; Optoelectronics -- Materials